Acrylamide derivatives of starch in two-phase systems used for purification of proteins. Part II. The use for purification of the wheat flour derived alpha-amylase inhibitor - Brzozowski, Z.; Pietruszka, N.; Galae, v I.; Mattiasson, B. (Polimery, 2022)
Preparation and properties of vinyl imidazole (VI)/vinyl caprolactam (VCL) copolymers and their complex compounds with copper(II) are described, which are capable of selectively separating some proteins in mixtures. The temperature of precipitation of these copolymers from aqueous solutions (Figs. 1-3) was studied in relation to the pH and NaCl content in the solution. A method was developed to prepare a Cu(II)-VI/VCL 10:90* complex able to form a two-phase system with starch acrylamide derivatives (APS) in the presence of NaCl. The two-phase system containing the Cu(II)-VI/VCL = 10:90* complex and an S/AA = 80:60 APS was found to help isolate a pure a-amylase inhibitor from wheat flour in 75% yield (Table 2). The acrylamide derivatives of starch were considered to be excellent cheap substitutes for expensive dextran and useful for the purification of various substances in aqueous two-phase systems.